Water - Leask, Nigel (Romanticism on the Net, 2023)
The essay opens by reflecting on the elemental qualities of water and its manifold cultural meanings in Western art and literature as well as in other exhibits in RÊVE (Romantic Europe: The Virtual Exhibition). Keats’s fascination with water, famously engraved on his epitaph in Rome, is linked to his Scottish tour of 1818 and his undescribed visit to the Falls of Foyers. The Scottish Highland tour was an open-air museum, linking up a series of spectacular waterfalls. Symptomatic of a new fascination with waterfalls shown by eighteenth-century garden designers and landscape painters, these watery spectacles aroused sublime euphoria in Romantic writers and picturesque tourists. Landowners capitalised on the Romantic obsession with waterfalls in establishing viewing sites and tourist infrastructure. Despite their ornamental and non-utilitarian nature, cascades demonstrated the “power” of water, a major energy source in the early pre-carbon industrial age. The second part of the essay analyses the reactions of a selection of literary tourists, from Dr Johnson to Sarah Murray and Coleridge, to the celebrated Falls of Foyers, opened up to tourism by Roy’s military road through the Highlands, and later by Telford’s Caledonian Canal. An afterward explores the demise of Foyers as a tourist site and its transformation into an industrial landscape.